UNVEILING KING ASOKA’S LEGACY: CRITICAL STUDY ON THE CONTENTS, LANGUAGES AND OBJECTIVES OF ASOKA’S INSCRIPTIONS - Medhācitto, Tri Saputra; Pannaloka, Deniyaye; Barua, Satyajit (Jurnal Pencerahan, 2024)
This research aims to provide a comprehensive understanding on the Asoka’s inscriptions, examining the contents, languages and objectives of the inscriptions. This research is a qualitative research carried out with library approach, in which the data are gathered from sources like books, journals, articles and relevant researches by scholars. The Buddhist literatures including Sri Lankan chronicles are also used to provide the information about the figure of King Asoka and his contributions to Buddhism. This research proves that the King Asoka was a significant figure in the Indian history, who was recognized for his impactful reign and advocacy for Buddhism. The archaeological discoveries, including inscriptions scattered across India, offer substantial historical insights into Asoka's reign and his endeavors. In his reign, the king utilized inscriptions as a means to disseminate his message of peace and harmony. The purpose of those inscriptions was to establish the Dhamma or righteousness teachings to the society. The Asoka’s inscriptions are dispersed across various locations in India, Nepal, Pakistan, and Afghanistan, with notable findings in places like Kalsi, Sopara, Mount Girnar, Yerragudi, Dhauli, and Jaugada, composed in languages like Prakrit, Greek, and Aramaic, are preserved in various scripts such as Brāhmī, Kharosthi, Greek, Aramaic, and bilingual Greek-Aramaic.